2018
DOI: 10.1038/s41594-018-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-associated histone pruning demarcates macroH2A chromatin domains

Abstract: The histone variant macroH2A occupies large repressive domains throughout the genome, however mechanisms underlying its precise deposition remain poorly understood. Here, we characterized de novo chromatin deposition of macroH2A2 using temporal genomic profiling in murine-derived fibroblasts devoid of all macroH2A isoforms. We find that macroH2A2 is first pervasively deposited genome-wide at both steady state domains and adjacent transcribed regions, the latter of which are subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 77 publications
4
46
0
Order By: Relevance
“…A recent study showed that the de novo incorporation of MacroH2A is genome-wide. It is then removed from transcribed chromatin in a transcription-associated mechanism, leading to the specific localization at repressed chromatin (44). Our data may be able to explain why this two-step mechanism is needed for MacroH2A localization in closed chromatin.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study showed that the de novo incorporation of MacroH2A is genome-wide. It is then removed from transcribed chromatin in a transcription-associated mechanism, leading to the specific localization at repressed chromatin (44). Our data may be able to explain why this two-step mechanism is needed for MacroH2A localization in closed chromatin.…”
Section: Discussionmentioning
confidence: 78%
“…At time of writing the mechanisms underlying the connection between PRC2 and MacroH2A during XCI are unknown. MacroH2A is enriched at H3K27me3 enriched chromatin throughout the genome (reviewed in 45), but appears to be established independently (46). It remains to be determined whether MacroH2A directly interacts with XIST; however, the lack of its presence in the interactome screens may implicate intermediate factors, which perhaps bind upstream of the D repeat (26,29,39,47).…”
Section: Discussionmentioning
confidence: 99%
“…We used Lsh−/− and Lsh+/+ MEFs (Fig. 3a) 12,49 , since they expressed higher levels of macroH2A1.2 compared to ES cells and since differentiated cells are known to express more macroH2A2 compared to ES cells ( Supplementary Fig. 4a) 13,[45][46][47] .…”
Section: Lsh Tethering Induces Transcriptional Repressionmentioning
confidence: 99%